Diagnostic accuracy of a lung ultrasound protocol (Vet BLUE) for detection of pleural fluid, pneumothorax and lung pathology in dogs and cats. (26th January 2021) - Cole, L.; Pivetta, M.; Humm, K.
Abstract : Objectives: To assess the accuracy of the lung ultrasound protocol Vet BLUE, using thoracic CT as the reference standard, for the detection of thoracic pathology in dogs and cats. Materials and Methods: Animals that had thoracic ultrasound and thoracic CT were prospectively recruited between May 2017 and September 2018. The Vet BLUE protocol was performed on animals at the time of admission by veterinarians with basic training in emergency ultrasound. A board‐certified radiologist, blinded to the Vet BLUE findings, reviewed the CT images. Results: CT was abnormal in 64.5% (20/31) animals. The number of CT sites positive for alveolar‐interstitial syndrome was 24.2% (60/248). When using CT as the reference standard, detection of ≥3 B lines with thoracic ultrasound had a sensitivity of 18.33% and specificity of 98.4% for detection of site specific alveolar‐interstitial syndrome. The sensitivity of Vet BLUE to detect alveolar‐interstitial syndrome increased to 56.9% when including the presence of any B line as abnormal. Overall accuracy for detection of alveolar‐interstitial syndrome based on these two criteria was 79% and 73%, respectively. Vet BLUE correctly identified consolidation in 58.3% (14/24) sites, pleural effusion in 66.6% (2/3) cases, pneumothorax in 33.3% (1/3) cases and intrathoracic mass in 25% (1/4) cases. Clinical Significance: The Vet BLUE protocol is a useful technique to detect alveolar‐interstitial syndrome and other thoracic pathology but should not be used as a sole imaging method. Detection of ≥3 B lines is highly suggestive of alveolar‐interstitial syndrome and warrants further diagnostics.